2013
DOI: 10.1002/jcb.24578
|View full text |Cite
|
Sign up to set email alerts
|

L-cysteine and hydrogen sulfide increase PIP3 and AMPK/PPARγ expression and decrease ROS and vascular inflammation markers in high glucose treated human U937 monocytes

Abstract: Diabetic patients have lower blood levels of L‐cysteine (LC) and hydrogen sulfide (H2S) and a higher incidence of vascular inflammation. This study examined whether impaired LC or H2S levels affect vascular inflammation markers in diabetes. Human U937 monocytic cells were treated with high‐glucose (HG, 25 mM, 20 h) in the presence or absence of LC (100, 500, or 1,000 µM, an endogenous precursor of H2S) or Na2S (5 or 25 µM, an exogenous source of H2S). Both LC and Na2S supplementation decreased intracellular RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 79 publications
3
42
0
Order By: Relevance
“…H 2 S has also been shown to have powerful antioxidant properties. Exogenous H 2 S attenuates the hyperglycemia-induced enhancement of ROS formation in endothelial cells and human U937 monocytes (8,28). In line with these findings, we observed that H 2 S decreased superoxide generation in macrophages and endothelial cells cultured with HG+ox-LDL.…”
Section: Discussionsupporting
confidence: 87%
“…H 2 S has also been shown to have powerful antioxidant properties. Exogenous H 2 S attenuates the hyperglycemia-induced enhancement of ROS formation in endothelial cells and human U937 monocytes (8,28). In line with these findings, we observed that H 2 S decreased superoxide generation in macrophages and endothelial cells cultured with HG+ox-LDL.…”
Section: Discussionsupporting
confidence: 87%
“…Fig. 9 demonstrates that exogenous supplementation with 1,25-dihydroxyvitamin D 3 , an active form of vitamin D, up-regulates both CSE protein expression and its activity as well as H 2 S levels in PBMC treated with either HG alone or in combination with AA, suggesting a positive effect of vitamin D on H 2 S homeostasis in diabetes.…”
Section: Role Of Hyperglycemia and Hyperketonemia On Cse Expression Imentioning
confidence: 95%
“…This indicates that the signaling and effector pathways downstream from H 2 S are not impaired significantly in experimental models used in the current study. It must be noted that, depending on the experimental conditions and models used, the other H 2 S-producing enzyme systems also have been shown to be affected by diabetes and diabetic complications (8)(9)(10)(11)(12)(13)(14)(15)(65)(66)(67); overviewed in [67]). Thus, it is likely that there is a complex dysregulation of the H 2 S system in diabetes, the nature of which depends on the model used, as well as the stage and severity of the disease.…”
Section: M P a I R M E N T O F T H E 3 -M S T / H 2 S P A T H W A Ymentioning
confidence: 99%
“…It exerts protective effects against hyperglycemic stress in the vascular endothelium and exhibits protective effects in animal models of diabetic complications (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%